Tinjauan Kesejahteraan Guru Honorer Melalui Standar Gaji Yang Sesuai Prinsip Ekonomi Islam Berbasis Maqasid Syari`ah - Faizah, Faizah; Kurniawati, Iin Rahmah (Faculty of Islamic Studies, University of Muhammadiyah Jakarta, 2026)
This study examines the welfare of honorary teachers from an Islamic economic perspective by analyzing fair wage standards through the framework of Maqasid al-Shari‟ah, particularly hifz al-nafs (protection of life), hifz al-mal (wealth), hifz al-„aql (intellect), and hifz al-din (religion). Employing a descriptive qualitative approach, the study draws on documentary data from academic literature, policy reports, and online news sources, which were analyzed using the Miles and Huberman model. The findings indicate that wage levels below the minimum standard, reliance on delayed school operational funds, and employment insecurity are associated with psychological stress, household vulnerability, limited access to adequate housing, constraints on professional development, and weakened religious commitment among honorary teachers. From a maqasid perspective, these conditions suggest misalignment with Islamic principles of wage justice, as reflected in the Prophetic injunction to provide timely and sufficient compensation to workers. Conceptually, this study contributes to Islamic economic discourse by positioning Maqasid al- Shari‟ah as an evaluative framework for assessing wage fairness and holistic welfare in the education sector, emphasizing falah and social justice as normative objectives.